2018
DOI: 10.1111/jphs.12220
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization evaluation among an elderly population: a retrospective cross-sectional study in a tertiary care hospital in Pakistan

Abstract: Objectives Ageing and its associated physiological changes make elderly more prone to chronic diseases, ultimately leading to escalated drug use. The aim of this study was to execute retrospective drug utilization evaluation among elderly patients discharged from the hospital. Methods A descriptive, retrospective, cross‐sectional study design was employed. Data were collected from the medical records of discharged elderly patients admitted between July 2016 and December 2016 in Bahawal Victoria Hospital, Bahaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Another study conducted in Karachi, Pakistan had revealed that at least 1 PIM was prescribed to more than half (64%) of the older population [ 46 ]. It is suggested that many of the PIMs like antihistaminic agents (e.g., diphenhydramine), proton pump inhibitors (e.g., omeprazole and esomeprazole) and analgesics (e.g., aspirin and non-steroidal anti-inflammatory drugs (NSAIDS)) are more frequently used by older people than any other age group [ 47 , 48 , 49 ]. This might be attributable to the reason that old age people mostly suffer from insomnia, heart burn, acid reflex, headache, muscle pain, and joint pain due to multiple co-morbidities and the physicians in developing countries like Pakistan are usually inefficient in diagnosing the underlying cause [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Karachi, Pakistan had revealed that at least 1 PIM was prescribed to more than half (64%) of the older population [ 46 ]. It is suggested that many of the PIMs like antihistaminic agents (e.g., diphenhydramine), proton pump inhibitors (e.g., omeprazole and esomeprazole) and analgesics (e.g., aspirin and non-steroidal anti-inflammatory drugs (NSAIDS)) are more frequently used by older people than any other age group [ 47 , 48 , 49 ]. This might be attributable to the reason that old age people mostly suffer from insomnia, heart burn, acid reflex, headache, muscle pain, and joint pain due to multiple co-morbidities and the physicians in developing countries like Pakistan are usually inefficient in diagnosing the underlying cause [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“… 37 It is estimated that antihistaminic agents (eg, diphenhydramine), proton pump inhibitors (eg, omepra-zole and esomeprazole), and analgesics (eg, aspirin and nonsteroidal anti-inflammatory drugs) are more frequently used by elderly people than by any other age groups. 38 40 This is probably due to the reason that old age people mostly suffer from insomnia, heart burn, acid reflex, headache, muscle pain, and joint pain due to multiple comorbidities and the physicians in developing countries such as Pakistan are usually inefficient in diagnosing the underlying cause. 41 , 42 Also, there is no clinical guideline available in Pakistan for the diagnosis and management of diseases among geriatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is due to multifaceted issues in the establishment of healthcare system and the use of e-mails and video conferencing in the management of chronic diseases. In a country like Pakistan, where almost half of the population is illiterate and over two thirds (67%) of the population reside in rural areas [27], lack of education and poor socioeconomic status serve as contributing factors towards decreased capacity and willingness to use information technologies. Thus, the objective of this study is to assess the capacity and willingness of patients to use information technology for managing chronic diseases.…”
Section: Introductionmentioning
confidence: 99%